CONCENTRATION OF MIGRATION BY MARITAL STATUS: A TOPICAL STUDY IN WEST BENGAL - Das, Uday; Munda, Jadab; Mondal, Rahul (International Journal of Research -GRANTHAALAYAH, 2021)
Migration-study holds some classic question as like who migrate, why migrate and where to migrate. Migration researcher delegates their attention to summarizing the nature of migrants ('who') based on sex, age, and the caste to guide who migrate. Demographers do not pay much attention to the marital status of the migrants. The marital status of the migrants ('who') is a significant controlling factor on human mobility. Marriage is a monumental institution in population dynamics, which proximately determines the socio-economic behaviour of the individual. Marital status sometime works as an obstacle and an opportunity for migrants. This study attempts to discover pattern and concentration of migration by marital status and sex to the district of West Bengal from different states and Union Territories (UTs) of India, enumerated by Place of Last Residence (POLR) in 2011, through cluster analysis. The present study finds ever married female migration is much higher than ever married male and never married migration is male-dominated. Marriage is the main reason for female migration, and job opportunities consist of male migration.